Practical Applications of Endoscopic Ultrasound-Guided Elastography: Core Principles, Techniques, and Pitfalls - Sonthalia, Nikhil; Tewari, Awanish; Roy, Akash; Ghoshal, Uday C.; Goenka, Mahesh K. (Journal of Digestive Endoscopy, 2025)
Recent advancements in endoscopic technology have established endoscopic ultrasonography (EUS) as a valuable tool for gastroenterologists. The integration of complementary imaging techniques, such as contrast enhancement and elastography, has significantly enhanced the capabilities of EUS. EUS-guided elastography (EUS-E) is an innovative imaging modality that improves the diagnostic accuracy of standard B-mode EUS by measuring the mechanical properties of tissues, particularly their elasticity or stiffness. These measurements are indicative of pathological changes and can aid in differentiating benign from malignant tissues. By combining elastography with EUS, it is now possible to assess tissue stiffness in organs such as the liver, pancreas, and lymph nodes. This approach not only aids in differential diagnosis but also enables the identification of the most accurate areas for EUS-guided tissue acquisition. EUS-E is performed using two main techniques: strain elastography and shear wave elastography, each with distinct advantages and limitations. This article provides an in-depth review of EUS-E, including its principles, techniques, clinical applications, and inherent limitations.
Keywords: endoscopic ultrasonography; EUS-guided elastography; shear wave elastography; liver stiffness; EUS-guided fine needle aspiration/biopsy